Zdystansowany inteligent. Emocje a afekt w poezji Barańczaka - Przymuszała, Beata Przymuszała (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article analyses Barańczak’s poetry to compare the cultural models of presenting emotions (especially characteristic to modernist poetry exploring emotional restraint) with the feeling of hurt and the resulting fear occasionally seen in his work: not expressed directly, yet affecting the perception of reality. The relation between emotions and affect powerfully shapes the image of the poetic persona in the poems of the author of Surgical Precision (Chirurgiczna precyzja), also affecting the literary language.